Analysing the effectiveness of migrants’ protection and integration through the applicability of the European Union’s directive on long-term residents - Ana Filipa NEVES; Carlos NOLASCO (Revista Jurídica Portucalense)
In 2003, the EU approved a new regime of long-term residency of third-country nationals who, after having lived in a Member State for a minimum of five years, should enjoy equal rights as those of Member States citizens in a wide range of economic and social matters. Only in 2011, was this specific regime also applied to refugees. Two decades after its entry into force, it was time to analyse the impact of this legal avenue in the lives of long-term migrants living in Portugal. The analysis conducted systematised how this EU legislation was transposed into the Portuguese migration and asylum legal norms and how it became effective in ensuring migrants’ well-being in Portugal. To this end, the chosen qualitative methodology included the analysis of legal and other relevant texts and, also, the organisation and conduction of semi-structured interviews and focus groups with migrants who were long-term residents in Portugal, in 2021. Drawing on the participants’ opinions, the present paper aims to address the advantages and pitfalls of long-term residence status in order to ameliorate the first and surpass the latter, not losing sight of the end goal of ensuring migrants’ rights to protection and inclusion.